Identification of Critical Success Factors for the Implementation of Mandarin-language ERP Software: A Case Study in a Manufacturing Company in Batam - Santoso, Didi; Eryc (LPPM & Fakultas Teknologi Informasi UNSAP, 2023)
As businesses increasingly adopt Enterprise Resource Planning (ERP) systems for improved performance, challenges associated with the implementation of Mandarin-language ERP software in a manufacturing company in Batam, Indonesia, have garnered significant attention. Using a qualitative research approach, this study conducted in-depth interviews with 27 employees familiar with the Mandarin-based ERP system. Thematic analysis was employed to understand the implications of language barriers and their impact on user performance. The research highlights key factors influencing the usability of Mandarin-language ERP systems, providing valuable insights for companies facing similar multilingual implementation challenges. The analysis emphasizes the crucial role of internal factors, including management involvement, commitment, training, and IT skills, in the successful implementation of Mandarin-language ERP systems. These findings serve as a practical guide for companies seeking to optimize internal processes and strengthen technological capabilities, facilitating smooth integration and utilization of ERP systems.